Karbon Tersimpan Pada Hutan Kota Bumi Saniari Kabupaten Teluk Bintuni - Siprianus Manibuy; Julius D. Nugroho; Anton S. Sinery (Program Pascasarjana Universitas Papua, 2021)
An urban forest is a collection of trees growing among buildings and people where they can protect the city as the functional traits. Forests are playing an important role in stabilizing CO2 concentrations in the atmosphere. As forest is a source of CO2 emissions, forests are also able to absorb and store CO2, so we could estimate the amount of CO2 absorbed by forest trees by calculating their biomass. This study aims to obtain the amount of carbon stock stored in the City Forest of Bumi Saniari, Teluk Bintuni Regency. Carbon stock was calculated to obtaine aboveground carbon (AGB), below ground carbon (BGB) and litter carbon (CS). In this study no measurements were made of soil carbon. The method used in this research is descriptive method and field survey with measurements using the nondestructive method. The results obtained were 801.52 tons of stored carbon above ground (AGB), the soil surface / litter (CS) is 273.54 tons C. The total carbon stock is 10 hectares of 1,411.69 tons C.